On the introduction of Citrostichus phyllocnistoides (Narayanan) in Sicily and its simultaneous rearing with Semielacher petiolatus (Girault) (Hym. Eulophidae) under seminatura/ climatic conditions (Bollettino di zoologia agraria e bachicoltura, 2024)
In order to stress the natural contro! agains citrus Leaf Miner (CLM) Phyllocnistiscitrella Stainton in Sicily, during 1999 Citrostichus phyllocnistoides(Narayanan) has ben introduced and released in the field. It was bred togetherwith Semielacher petiolatus (Girault) under seminatura! conditions. During therearing it was observed that no competion between the two parasitoids occurredand that both species survived and multiplied although the temperature lastedabove 40°C for many hours and in severa! days.The results emerged from the releases of C. phyllocnistoides in some CLM' infestedcitrus groves look not only at its recoveries, but also at its probable establishmentin Sicily.
Keywords: Citrostichus phyllocnistoide; CLM' natural control